"Because the country, it seems though, has turned their back on me": Experiences of institutional betrayal among veterans living with Gulf War Illness. (September 2021) - Bloeser, Katharine; McCarron, Kelly K.; Merker, Vanessa L.; Hyde, Justeen; Bolton, Rendelle E.; Anastasides, Nicole; Petrakis, Beth Ann; Helmer, Drew A.; Santos, Susan; Litke, David; Pigeon, Wilfred R.; McAndrew, Lisa M.
Abstract: People living with medically unexplained symptoms (MUS) often have poor quality of life and health outcomes. Many struggle to engage with and trust in healthcare systems. This qualitative study examined how experiences with institutions influence perceptions of medical care for MUS by applying the theoretical framework of institutional betrayal to narratives of U.S. military Veterans living with Gulf War Illness (GWI). Institutional betrayal refers to situations in which the institutions people depend upon for safety and well-being cause them harm. Experiences of institutional betrayal both during active military service and when first seeking treatment appeared to shape perceptions of healthcare in this sample. Veterans expressed the belief that the military failed to protect them from environmental exposures. Veterans' concerns regarding subsequent quality of healthcare were intrinsically linked to a belief that, despite official documentation to the contrary, the predominant paradigm of both the U.S. Department of Defense and the U.S. Department of Veterans Affairs (VA) is that GWI does not exist. Veterans reported that providers are not adequately trained on treatment of GWI and do not believe Veterans' descriptions of their illness. Veterans reported taking up self-advocacy, doing their own research on their condition, and resigning themselves to decrease engagement with VA healthcare or seek non-VA care. The study's findings suggest institutional level factors have a profound impact on perceptions of care and the patient-provider relationship. Future research and policy aimed at improving healthcare for people living with MUS should consider the concept of institutional betrayal. Highlights: Institutional betrayal can occur when institutions fail to protect constituents from harm. Veterans living with Gulf War Illness describe institutional betrayal in healthcare. Veterans sometimes give-up on healthcare because of these experiences. Institutions, as well as individual providers, must address institutional betrayal.